Evil is still evidence: comment on Almeida - Bass, Robert H. 195X- (Religious studies, 2024)
Michael Almeida has recently tried to show that if S5 correctly represents metaphysical necessity, there can be no non-trivial evidence for or against the existence of the traditional God. Evidence would thus be irrelevant to the reasonability of traditional theistic belief. Almeida's argument has implications beyond its announced target: it amounts to a new argument for sweeping scepticism. Almeida's argument for the irrelevance of evidence to the existence of God would apply to any state of affairs that entails some metaphysical necessity. In S5, every state of affairs entails some metaphysical necessity, so Almeida should conclude that non-trivial evidence for or against any state of affairs is impossible. I argue that the problem is not with S5 but with inadequately motivated assumptions about evidential support. Avoiding those assumptions disables the argument for sweeping scepticism and without foreclosing the possibility of non-trivial evidence for or against the existence of the traditional God.